Primary intestinal lymphangiectasia in adults – diagnostic and therapeutic challenge - Jocic, Tatiana; Latinovic Bosnjak, Olgica; Zivojinov, Mirjana; Stojsic, Mirjana; Ilic Sabo, Jelena (Vojnosanitetski pregled, 2020)
Introduction. Primary intestinal lymphangiectasia is a rare disorder, characterized by abnormal dilation of intestinal lymphatic vessels and extensive enteric loss of lymph rich in plasma proteins, lymphocytes and chylomicrons. The main characteristics of the disease are hypoalbuminemia, hypogammaglobulinemia, lymphocytopenia, and more rarely, the deficit of liposoluble vitamins and anemia. Except for primary, there are secondary lymphangiectasia, associated with celiac disease, malignant, infective and inflammatory diseases of the small intestine, fibrosis, liver and cardiovascular diseases. Case report. A male, 33 years of age, presented for his medical examination suffering from diarrhea and edema. The diagnosis was established upon the histological examination of a small intestine biopsy during double balloon enteroscopy, which revealed changes only in one segment of the intestine examined. Such a finding was later confirmed by the video endoscopy capsule. Conclusion. The diagnosis of intestinal lymphangiectasia is usually established before the age of 3, but it can also be diagnosed in adults. The diagnosis is based on the histological analysis of the intestinal mucosa biopsy, obtained by endoscopic procedures. The diagnosis of primary intestinal lymphangiectasia is also made upon the exclusion of secondary causes.